IS TOURISM DEVELOPMENT A BENEFICIAL ASPECT IN THE EYES OF THE LOCAL COMMUNITY? - Valentin ȘERBAN; Adrian TUREK-RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural development is a key objective of national and European policies, widely debated at political level but also in the academic community. Romania is a predominantly agricultural country which makes agriculture the main pillar of rural development. However, there are many rural areas in the mountains where agriculture cannot be practised at a high performance level, so diversification and the search for new economic sectors is essential. In these areas, tourism can be considered as an alternative to agriculture in rural development. It is important that tourism development is managed responsibly and that the views and concerns of local people are taken into account. Open dialogue and community consultation can help strike a balance between the economic benefits of tourism and the preservation of local values and quality of life. In this context, this paper aimed to carry out a survey in order to identify the opinion of the local population from the commune of Valea Doftanei in relation to the development of tourism and leisure activities as a source of income and with a positive impact on the community development. The survey was based on an interview using a structured questionnaire and addressed to 380 interviewees and the results have been statistically processed with SPSS Software. The results pointed out that the inhabitants of Valea Doftanei Commune have a positive attitude towards the development of tourism and leisure activities and consider that by a well managed tourism strategy it could be assured a beneficial economic development of the locality as well as the preservation of local values and quality of life.